Prospects and challenges of CAR-T cell therapy combined with ICIs - Lv, Yufan; Luo, Xinyu; Xie, Zhuoyi; Qiu, Jieya; Yang, Jinsai; Deng, Yuqi; Long, Rou; Tang, Guiyang; Zhang, Chaohui; Zuo, Jianhong (Frontiers in Oncology, 2024)
Immune checkpoint molecules are a group of molecules expressed on the surface of immune cells that primarily regulate their immune homeostasis. Chimeric antigen receptor (CAR) T cell therapy is an immunotherapeutic technology that realizes tumor-targeted killing by constructing synthetic T cells expressing specific antigens through biotechnology. Currently, CAR-T cell therapy has achieved good efficacy in non-solid tumors, but its treatment of solid tumors has not yielded the desired results. Immune checkpoint inhibitors (ICIs) combined with CAR-T cell therapy is a novel combination therapy with high expectations to defeat solid tumors. This review addresses the challenges and expectations of this combination therapy in the treatment of solid tumors.